An Investigation of the Users’ Continuance Intention of Using Mobile Applications: Roles of the Application Quality and Usability - GE, JUN (The Graduate School, Ajou University, 2017)
Over the last few years, Smartphone had increased their presence in the every day life. With the rapid growth of mobile network technologies, allowing users to browse or search the internet information with their smart phones, downloading mobile applications, videos and games at the same time. Although various research of studying mobile application with acceptance or purchase intention for paid applications are available. But there is little empirical research focused solely on users’ continuance intention to use mobile application. The present study sets to address this omission, the purpose of this paper is to investigate the important influence factors of users’ continuance intention to use mobile application; it investigates the impacts of application personality (enthusiasm, genuineness, sophistication and unpleasantness) and user perception (aesthetic, ease of use and perceived control) on application quality and usability respectively, which in turn influence users’ continuance intention to use mobile application. An integrated research model was developed, application personality, user perception, application quality and usability were measured by multiple dimensions. This research conducted empirically analysis with data collected from 527 users of smartphones in China. Results show that all dimensions of application personality and user perception have significant and positive influence on application quality and usability respectively, except unpleasantness, which has significant and negative influence on application quality. Besides application quality and usability have significant and positive influence on users’ continuance intention to use mobile application. Furthermore, it would provide some insights as to how application developers can improve the quality and usability of the service to maintain or enhance users’ loyalty.
학위논문(석사)--아주대학교 일반대학원 :경영정보학과,2017. 2
Keywords: Mobile Application; Application Personality; User perception; Application Quality; Application Usability; Continuance Intention